2020
DOI: 10.1186/s13062-020-00280-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Crohn’s disease inflammation and recurrence

Abstract: Chron’s Disease is a chronic inflammatory intestinal disease, first described at the beginning of the last century. The disease is characterized by the alternation of periods of flares and remissions influenced by a complex pathogenesis in which inflammation plays a key role. Crohn’s disease evolution is mediated by a complex alteration of the inflammatory response which is characterized by alterations of the innate immunity of the intestinal mucosa barrier together with a remodeling of the extracellular matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 97 publications
0
75
0
9
Order By: Relevance
“…Evidences have confirmed that CD is a chronic inflammatory intestinal disease, which is caused by an unrestrainable immune response against luminal bacterial antigens. The role of inflammatory cells infiltrating in maintaining an active stage is well established and most of the therapeutic strategies are aiming to block the cascade of inflammatory reaction and release of proinflammatory cytokines (14,15). In the present study, by analyzing the data for CD, non-inflammatory tissues, and normal intestinal tissues using ssGSEA, we described the landscape of immune infiltration in CD and found that the fraction of 16 immune cells was significantly different among these three kinds of tissues.…”
Section: Discussionmentioning
confidence: 70%
“…Evidences have confirmed that CD is a chronic inflammatory intestinal disease, which is caused by an unrestrainable immune response against luminal bacterial antigens. The role of inflammatory cells infiltrating in maintaining an active stage is well established and most of the therapeutic strategies are aiming to block the cascade of inflammatory reaction and release of proinflammatory cytokines (14,15). In the present study, by analyzing the data for CD, non-inflammatory tissues, and normal intestinal tissues using ssGSEA, we described the landscape of immune infiltration in CD and found that the fraction of 16 immune cells was significantly different among these three kinds of tissues.…”
Section: Discussionmentioning
confidence: 70%
“…The CSU and CD have a strong autoimmune involvement with an increase of proinflammatory cytokines (20). One common thread in the pathophysiology of both diseases is the imbalance in cytokine levels, in particular for IL-17 and TNF-a (21-23).…”
Section: Discussionmentioning
confidence: 99%
“…Crohn's disease (CD) is an idiopathic, incurable chronic inflammatory disease of the GI tract [92][93][94][95], associated in more than 30% of cases to symptoms of perianal disease (PAD) [96][97][98]. The risk of developing PAD is consistent with the time from the diagnosis of CD, from 20% after ten years and up to 30% after twenty years.…”
Section: Perianal Crohn's Diseasementioning
confidence: 99%